Genome-wide mRNA analysis reveals a TUBD1 isoform profile as a potential biomarker for diabetic retinopathy development - Villegas-Ruiz, Vanessa; Hendlmeier, Ferdinand (Experimental eye research, 2017)
Diabetic retinopathy (DR) affects approximately one third of all diabetic subjects and is the leading cause of blindness in young to middle-aged adults in the developed world. While early diagnosis is crucial for preventing DR-associated visual loss, the identification of accessible biomarkers that could lead to presymptomatic recognition of the disease is of great clinical importance. The aim of this work was to investigate the possible involvement of alternative splicing events in DR development by performing a genome-wide transcriptional profiling comparing blood-derived RNA from DR subjects and from diabetic-non DR controls. A total of 95 RNA samples, 67 from patients with bilateral DR and 28 from diabetic patients without DR after a period of at least 10 years with type 2 DM, were compared in a genome-wide transcriptome analysis using the GeneChip® Human Gene 2.0 ST Array which contains probe sets covering all exons of ∼33,500 coding transcripts of annotated genes. Microarray data analysis followed by RT-PCR and cDNA sequencing identified important differential splicing events in TUBD1 (Tubulin, Delta-1) isoforms between DR and DM samples. Specifically, the co-expression of particular TUBD1 isoforms was significantly associated with NPDR risk (p = 0.039 by Pearson's chi-squared test; OR (CI 95%): 8.1 (1.0-72.7)). Analysis of TUBD1 signal pathways and regulating networks using a MetaCore platform showed that HIF-1, a molecule playing an important role in the pathogenesis of DR, is a direct regulator of TUBD1 expression. In conjunction, our data suggest that TUBD1 mRNA isoform expression profile in peripheral blood could be an accessible biomarker for predicting the risk for diabetic retinopathy development.
Gesehen am 13.09.2018